Aprendemos a producir parbolas de manera colaborativa - Silup Mauriola, Luz Anglica (2022)
The present Work of Professional Sufficiency We learn to produce parables in a collaborative way, allows the teacher to detail both the theoretical and pedagogical support that they use in their teaching practice, since it is a systematic reflection of the teacher's work. Likewise, it is made clear that the learning session responds to an entire implication of factors, such as the pedagogical approach, where a theoretical framework centered on the student is assumed, since learning is based on the currents proposed by Piaget, Vygotsky Ausubel and Brunner to name a few. On the other hand, the teacher, when interacting with the students, uses a whole set of methodological strategies, media, educational materials and an evaluation approach, this work details these elements, as well as explains how the formative evaluation guides the entire development of the session of learning about the parables of Jesus. Finally, the teacher proposes her conclusions from the reflection of her pedagogical practice carried out.